'Seriously, get out': Feminists on the forums and the War(craft) on women. (August 2014) - Braithwaite, Andrea
Everyday gendered experiences provide an affective framework for understanding participation in massively multiplayer online games (MMOGs) and their community forums. Debates on the World of Warcraft online forums about changes to an upcoming in-game character named Ji Firepaw, who initially greeted characters with gendered and sexist dialogue, demonstrates how games and game communities are embedded in larger cultural contexts. Themes like the feminist as killjoy, anxious masculinity and player agency recur across official and unofficial WoW forums regarding Ji Firepaw. These concerns rely upon and aim to reinforce gendered power dynamics, illustrating how the digital and the virtual are not independent spaces. Rather, MMOGs and their associated online environments are experienced as part of the everyday, such that feminists and feminism are treated as threats to these virtual spaces and, by extension, to the enjoyment and sociability of an implicitly broader set of shared values about gender and sex roles.